KREATIFITAS GURU PAI DALAM MENINGKATAKAN MOTIVASI BELAJAR SISWA - Latifatul Mahbubah; Mastuhah Mastuhah; Shofiyatun Nisa; Siti Nikmatul Laili; Mudmainnah Mudmainnah (Tarbawi, 2021)
A teacher's creativity is important for the teaching and learning process to run well. Teacher creativity is also important in achieving student learning outcomes. This research aims to determine teacher creativity in efforts to increase student motivation when learning. This research is a qualitative descriptive research in which data collection was obtained by observation, interviews and documentation. From the results of this research, the author can conclude that teacher creativity in increasing student learning motivation is effective in increasing student motivation, this is proven by the increase in student learning outcomes at the end of the semester by getting grades above the average. Other evidence can be seen from the students' activeness when participating in the teaching and learning process even though there is a lack of school facilities.